Survey of Households in Five Judicial Districts of the United States: A Civil Litigation Project, 1977-1979 - Trubek, David ([Verlag nicht ermittelbar], 1992)
This data collection is based on the household screening survey conducted by the Civil Litigation Research Project (CLRP) in 1980. The survey was conducted in five federal judicial districts in the United States: Eastern Wisconsin, Eastern Pennsylvania, South Carolina, New Mexico, and Central California. The primary objective of the study was to identify individuals involved in disputes that might have become lawsuits. The major area of investigation was claiming behavior. The dataset also includes 54 households from the "screened experiment," whereby households known to have been involved in lawsuits were contacted. Demographic variables include the age, sex, education, occupation, and union status of the chief wage earner. Also included are the respondent's sex, race, and family income. Questions were asked about consumer problems, problems with persons who owed the respondent money, discrimination problems, debt problems, property-related problems, mortgage-related problems, landlord-tenant problems, problems with government benefits, and post-divorce problems. The unit of analysis is the household.